Oral commensal bacteria differentially modulate epithelial cell death. (December 2020) - White, Tyresia; Alimova, Yelena; Alves, Vanessa Tubero Euzebio; Emecen-Huja, Pinar; Al-Sabbagh, Mohanad; Villasante, Alejandro; Ebersole, Jeffrey L.; Gonzalez, Octavio A.
Highlights: Epithelial cell death is a regulatory process of inflammation and tissue homeostasis. Oral commensal bacteria differentially regulate epithelial cell death. Some oral commensal bacterial species likely contribute to oral inflammation. Oral epithelial cell death appears to be poorly induced by periodontopathogens. Abstract: Objective: Epithelial cell death is an important innate mechanism at mucosal surfaces, which enables the elimination of pathogens and modulates immunoinflammatory responses. Based on the antimicrobial and anti-inflammatory properties of cell death, we hypothesized that oral epithelial cell (OECs) death is differentially modulated by oral bacteria. Material and Methods: We evaluated the effect of oral commensals Streptococcus gordonii (Sg), Streptococcus sanguinis (Ss), and Veillonella parvula (Vp), and pathogens Porphyromonas gingivalis (Pg), Tannerella forsythia (Tf), and Fusobacterium nucleatum (Fn) on OEC death. Apoptosis and necrosis were evaluated by flow cytometry using FITC Annexin-V and Propidium Iodide staining. Caspase-3/7 and caspase-1 activities were determined as markers of apoptosis and pyroptosis, respectively. IL-1β and IL-8 protein levels were determined in supernatants by ELISA. Results: Significant increases in apoptosis and necrosis were induced by Sg and Ss. Pg also induced apoptosis, although at a substantially lower level than the commensals. Vp, Tf, and Fn showed negligible effects on cell viability. These results were consistent with Sg, Ss, and Pg activating caspase-3/7. Only Ss significantly increased the levels of activated caspase-1, which correlated to IL-1β over-expression. Conclusions: OEC death processes were differentially induced by oral commensal and pathogenic bacteria, with Sg and Ss being more pro-apoptotic and pro-pyroptotic than pathogenic bacteria. Oral commensal-induced cell death may be a physiological mechanism to manage the extent of bacterial colonization of the outer layers of mucosal epithelial surfaces. Dysbiosis-related reduction or elimination of pro-apoptotic oral bacterial species could contribute to the risk for persistent inflammation and tissue destruction.